Cervical and Ocular Vestibular-Evoked Myogenic Potentials in Patients With Intracochlear Schwannomas - Fröhlich, Laura; Curthoys, Ian S.; Kösling, Sabrina; Obrist, Dominik; Rahne, Torsten; Plontke, Stefan K. (Frontiers in Neurology, 2020)
Objective: To evaluate ocular and cervical vestibular evoked myogenic potentials (oVEMPs and cVEMPs) in patients with solely intracochlear localization of an intralabyrinthine schwannoma (ILS). Study design: Retrospective analysis of a series of cases. Setting: Monocentric study at a tertiary referral center. Patients: Patients with intracochlear schwannoma (ICS) and VEMP measurements. Outcome Measures: Signed asymmetry ratio (AR) of cVEMPs and oVEMPs to air conducted sound with AR cut-offs considered to be asymmetrical when exceeding ±30% for cVEMPs and ±40% for oVEMPs with respect to the side affected by the tumor (reduced amplitudes on the affected side indicated by negative values, enhanced amplitudes by positive values); VEMP amplitudes and latencies; tumor localization in the cochlear turn and scala. Results: Nineteen patients with a solely intracochlear tumor (ICS patients) (10 males, 9 females, mean age 57.1 (SD: 13.4) years) were included in the study. On the affected side, cVEMPs were absent or reduced in 47% of the patients, normal in 32%, and enhanced in 21%. Ocular VEMPs on the affected side were absent or reduced in 53% of the patients, normal in 32% and enhanced in 15%. Latencies for cVEMPs and oVEMPs were not significantly different between the affected and non-affected side. In all patients with enhanced VEMPs, the tumor was located in the scala tympani and scala vestibuli. Conclusions: As a new and unexpected finding, VEMP amplitudes can be increased in patients with intracochlear schwannoma, mimicking the third window syndrome.